The Relationship Between Learning Motivation And Student Readiness To Take Exams - Rostiana (Universitas Lancang Kuning, 2023)
The level of student learning outcomes is influenced by the readiness of students to take the exam. This study aims to examine the relationship between learning motivation and students' readiness to take exams. This research uses descriptive correlational method, data collection uses a questionnaire and is analyzed using the percentage formula and correlation test using SPSS 20.00. the sample is 72 with the sampling method using simple random sampling technique. The results of the study (1) the results of research findings on students' learning motivation are classified as moderate. (2) The research findings regarding students' readiness to take exams are classified as moderate , (3) there is a significant relationship between students' learning motivation and students' readiness to take exams. The implication of this research is that counselors provide guidance and counseling services that can minimize students who lack motivation to learn, so that students can develop their potential. The services that can be provided are information services, group counseling services, individual counseling services and other Counseling Guidance services. Then the school principal is to provide a minimum of 2 (two) hours per week for each class used by the counseling teacher to carry out the above activities.